Efektivitas Pendampingan dan Akses Bantuan Hukum Pro Bono dalam Penyelesaian Sengketa Hukum - Nagari, Cikal Gumiwang; Athaya, Raden Mas Agra Arinda; Siboro, Yevanya Sagita Purba; Togatorop, Agracecia Ebena; Sumardiana, Benny; Abidah, Shofriya Qonitatin (Media Hukum Indonesia (MHI), 2025)
Access to justice is a fundamental right guaranteed by the constitution and international legal instruments, but vulnerable groups in Indonesia such as the poor, people with disabilities, and victims of human rights violations often have difficulty obtaining legal assistance due to economic limitations and low understanding of the law. Pro bono legal aid provided free of charge by advocates or legal aid organizations is an important solution in bridging this gap. This article analyzes the role of pro bono legal assistance in improving access to justice through normative and empirical approaches, by examining Law No. 16/2011 and case studies of its implementation in various regions. The results show that pro bono legal aid has a positive impact, but is faced with challenges such as the lack of advocates involved, the limited capacity of legal aid institutions, and the lack of utilization of technology. Therefore, strengthening incentives, institutions, and digitalization are strategic steps to create a more inclusive and equitable justice system.